Global Research Trends and Risk Factors for Loneliness in Older Adults - Salsabila, Riskita Ayudira; Saki, Vernonia Yora; Nasution, Ahmad Azmi; Anggraini, Rizkianti; Putra, Onetusfifsi (Scripta Medica, 2026)
Loneliness was defined as an unpleasant feeling for a person when there is a gap between expectations of desired social connection with actual number of social relationships owned, both in terms of quantity or especially the quality. This research was systematic literature review with bibliometric analysis employs a two-phase quantitative approach. In the first phase, scientific publications were collected from two databases, there is Scopus and Web of Science (WoS). The analysis and visualization show that loneliness among older adults is an increasingly prominent topic in global research, especially since the COVID-19 pandemic. This research reveals that loneliness was closely linked to multidimensionality and was receiving attention from various fields, including neuroscience, behavioral health and geriatric care. The main themes of this research include psychological and cognitive factors, social isolation, and geriatric vulnerability.            Although the topic of loneliness among the elderly is gaining high attention in global academic interest, there was still a gap in innovative research, which calls for a multidisciplinary approach, especially in the discussion of risk factors for loneliness among the elderly. Some of the potential topics for further research are the relationship of loneliness among the elderly with socioeconomic factors, technology and digitalization, elderly care, religion and culture, and the direct relationship of loneliness with biomedical risks in geriatric clinical conditions such as atrial fibrillation, cognitive impairment, osteoporosis, and fall risk. These topics will open up great opportunities for researchers to contribute to and develop the advancement of this issue.
Keywords: Aged; Population; Loneliness; Risk